Effects of harvest date and additives on maize silage quality under boreal conditions - Rinne, Marketta; Franco, Marcia; Kuoppala, Kaisa; Jalava, Taina; Stefanski, Tomasz; Kokkonen, Tuomo (Agricultural and Food Science, 2024)
There is increasing interest in Finland to cultivate maize for silage, although the climatic conditions are in the borderline for maize due to the short and cool growing season. This may result in an immature crop that differs from typical maize for ensiling by having low dry matter (DM) and starch concentrations. We evaluated the preservation characteristics of forage maize during 2019 and 2020 harvested in Helsinki, Finland, at two stages of maturity. The DM concentration of the crops ranged from 230 to 360 g kg-1, and starch concentration from 179 to 283 g kg-1 DM. The crops were ensiled in laboratory scale using four different chemical organic acid based additives or a heterofermentative lactic acid bacteria inoculant. A control silage without additive treatment was also included. All silages were well fermented with low pH (average 3.75) and proportion of ammonia N in total N (average 47 g kg-1). Formic acid based additives restricted silage fermentation and most chemical additives improved the aerobic stability of maize silages compared to the control and inoculant treated silages that, under the conditions of the current study, did not differ from each other.